2010
DOI: 10.1074/jbc.m110.127993
|View full text |Cite
|
Sign up to set email alerts
|

The Sphingosine Kinase 1 Inhibitor 2-(p-Hydroxyanilino)-4-(p-chlorophenyl)thiazole Induces Proteasomal Degradation of Sphingosine Kinase 1 in Mammalian Cells

Abstract: Sphingosine kinase 1 (SK1) is an enzyme that catalyzes the phosphorylation of sphingosine to produce the bioactive lipid sphingosine 1-phosphate (S1P). We demonstrate here that the SK1 inhibitor, SKi (2-(p-hydroxyanilino)-4-(p-chlorophenyl)thiazole) induces the proteasomal degradation of SK1 in human pulmonary artery smooth muscle cells, androgen-sensitive LNCaP prostate cancer cells, MCF-7 and MCF-7 HER2 breast cancer cells and that this is likely mediated by ceramide as a consequence of catalytic inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
211
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(232 citation statements)
references
References 36 publications
21
211
0
Order By: Relevance
“…In contrast, SK1 protein levels were substantially reduced in cells exposed to SKI II (10 M) ( Fig. 1E ), which agrees with published reports in other cell models ( 65 ). Figure 2 summarizes the results of UPLC/TOFMS analyses of sphingolipids extracted from HGC 27 cells harvested at different time points after incubation with 10 M SKI II.…”
Section: Western Blottingsupporting
confidence: 80%
“…In contrast, SK1 protein levels were substantially reduced in cells exposed to SKI II (10 M) ( Fig. 1E ), which agrees with published reports in other cell models ( 65 ). Figure 2 summarizes the results of UPLC/TOFMS analyses of sphingolipids extracted from HGC 27 cells harvested at different time points after incubation with 10 M SKI II.…”
Section: Western Blottingsupporting
confidence: 80%
“…Importantly, we also found that SKI-I promotes the degradation of p62 through proteasome in AML cells. Consistently, activation of the proteasome machinery in response to SK inhibition has been reported (47). As the addition of bortezomib stabilized p62 and enhanced the autophagydependent activation of caspase-8 and apoptosis upon SKI-I treatment, inhibition of proteasome may be a key factor to increase the efficacy of SKI-I-induced cell death.…”
Section: Discussionsupporting
confidence: 48%
“…We have demonstrated that SKi induces the proteasomal degradation of SK1a and SK1b (which has an 86 amino-acid N-terminal extension compared to SK1a) in androgen-sensitive LNCaP prostate cancer cells and this results in a reduction in S1P levels and an increase in sphingosine and C22:0 and C24:0 ceramide levels and the induction of apoptosis (Loveridge et al, 2010). SKi also induces proteasomal degradation of SK1a in androgen-independent LNCaP-AI cells, but fails to reduce SK1b levels (Loveridge et al, 2010), which is possibly a consequence of a compensatory increase in SK1b mRNA expression in these cells. This is associated with a failure to increase C22:0 and C24:0 ceramide levels and the absence of apoptosis (Loveridge et al, 2010;Lim et al, 2012).…”
Section: Sk2 and T-all--acute Lymphoblastic Leukaemia Is The Most Commentioning
confidence: 99%
“…A common feature of these inhibitors is that they induce the ubiquitinproteasomal degradation of SK1 in solid cancer cell lines (Loveridge et al, 2010;Tonelli et al, 2010;Lim et al, 2011b) and proliferating vascular smooth muscle cells (Loveridge et al, 2010;Baek et al, 2013;Byun et al, 2013). This leads to inhibition of DNA synthesis (Byun et al, 2013) and is recapitulated by siRNA knockdown of SK1 expression.…”
Section: Sk2 and T-all--acute Lymphoblastic Leukaemia Is The Most Commentioning
confidence: 99%
See 1 more Smart Citation